Country risk perceptions and responses towards private-sector investments in renewable energy (re) in Sub-Saharan African countries: A comparative study of Tanzania and South Africa - Ndunguru, Benedict Henry (My University, 2018)
The sub-Saharan Africa (SSA) region possesses immense magnitudes of renewable energy (RE) resources, while at the same time suffering from low electrification rates. Faced with inadequacy of public-sector funding for scaling-up electrification, the respective governments face the daunting challenge of facilitating private-sector investor-participation in the sector. As a methodological strategy, the study hypothesised that sovereign credit ratings influence the level of participation of private sector investors in the SSA region and its countries. Based on a comparative case study method and a qualitative study approach (with primary data collected through interviews and secondary data captured from relevant national policies and sovereign credit risk reports), the study argues that the sovereign ratings and disjuncture in public sector responses to prevailing risk perceptions contribute to the varying RE-investment levels in the case study countries of Tanzania and South Africa. The study finds that sovereign credit-risk ratings by “cartel-like”, west-based credit-rating agencies influence country-risk perceptions of private-sector investors and consequently the level of RE-investments in SSA. The study also finds that country policy responses and compliance towards mitigation of private-sector investment risks are relatively weak in Tanzania compared to South Africa. The study substantiates on this finding through a comparison of the relatively low level of RE-investment in Tanzania compared to that of South Africa in reference to their respective country-risk profiles. As market opportunities are greater in Tanzania, differences in the risk perception profiles is argued to be the factor that primarily accounts for their contrasting level of RE-investments. The study therefore finds that high-risk perceived SSA countries are not systematically pursuing more convincing commitments to governance and policy certainty in order to improve on their private-sector risk-perception profiles especially as administered by risk rating agencies. Existing studies argue that such alignment could be deemed as detrimental to political autonomy as commonly argued by the region’s political regimes as well as political analysts, who often associate such ratings as hidden manipulations aimed at deepening the strangle-hold of neo-colonialism. It is therefore critical to extend the findings of this study on this persistent concern of SSA governments in order to expedite the unlocking of private-sector participation in RE-investment opportunities in the region which would in turn improve on the prevailing low electrification rates.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters of Architecture in Sustainable and Energy Efficient Cities. Johannesburg, 2018